Adverse effects of subcutaneous vs intravenous hydration in older adults: An assessor-blinded randomised controlled trial (RCT). (13th October 2021) - Danielsen, Mathias Brix; Worthington, Elisa; Karmisholt, Jesper Scott; Møller, Jørn Munkhof; Jørgensen, Martin Gronbech; Andersen, Stig
Abstract: Background: Hydration therapy is essential in the care of the older patient. Subcutaneous (SC) hydration is a relevant method for parenteral hydration, but clinical trials on the subject have methodological shortcomings compared to updated standards. Design: Assessor-blinded, non-inferiority RCT to explore if SC is a safe alternative to intravenous (IV) hydration. Participants: Eligible patients were: Admitted patients 65 years or older with a need for parenteral hydration. The targeted sample size was 67 patients in each group. Intervention: Patients were randomised to parenteral hydration via an IV or SC catheter during a 24 hours observation period. The non-randomised catheter (inactive) was placed as a sham on the patient, thereby blinding the caregivers and outcome assessors. Measurement: Our primary outcome was the proportion of patients reporting at least one adverse effect with a non-inferiority calculation using a 20% margin. Results: We included 51 patients, with 24 randomised to SC and 27 to IV. We were unable to reach our target sample size due to challenges in recruitment, time limitation, and COVID-19. For the outcome of adverse effects, SC was non-inferior to IV (p = 0.012). Time spent on inserting the catheters was shorter with SC (p = 0.001). The groups did not differ by pain of insertion, discomfort during infusion, or the risk of developing delirium. Conclusion: SC is a safe alternative to IV hydration, is faster to place and should be an available method for parenteral hydration wherever older adults are cared for. Trial registration: ClinicalTrials.gov Identifier: NCT03710408